2013
DOI: 10.1111/jcpp.12166
|View full text |Cite
|
Sign up to set email alerts
|

Life‐time prevalence and psychosocial correlates of adolescent direct self‐injurious behavior: A comparative study of findings in 11 European countries

Abstract: These results suggest high lifetime prevalence of D-SIB in European adolescents. Prevalence as well as psychosocial correlates seems to be significantly influenced by both gender and country. These results support the need for a multidimensional approach to better understand the development of SIB and facilitate culturally adapted prevention/intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
264
11
27

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(334 citation statements)
references
References 56 publications
32
264
11
27
Order By: Relevance
“…Der naturalistische Verlauf der Störung scheint durch erste Symptome in Pubertät, einen Erkrankungsgipfel in der späten Adoleszenz sowie einer linearen Abnahme im jungen Erwachsenen-Alter gekennzeichnet zu sein. Verfügbare Längsschnittbefunde geben Hinweise, dass BPS eine dynamische Erkrankungsgruppe mit allenfalls mittlerer Stabilität sind, und ein Prozentsatz zwischen 85-99 % der Betroffenen nach 10 Jahren auf der Symptomebene nahezu remittieren (Übersicht in [19,21] [24,25]. Im Gegensatz dazu berichten 30-50 % aller im stationären kinder-und jugendpsychiatrischen Hilfesystem befindlichen Jugendlichen, sich repetitiv selbst zu verletzen [26].…”
Section: Meta-analysenunclassified
“…Der naturalistische Verlauf der Störung scheint durch erste Symptome in Pubertät, einen Erkrankungsgipfel in der späten Adoleszenz sowie einer linearen Abnahme im jungen Erwachsenen-Alter gekennzeichnet zu sein. Verfügbare Längsschnittbefunde geben Hinweise, dass BPS eine dynamische Erkrankungsgruppe mit allenfalls mittlerer Stabilität sind, und ein Prozentsatz zwischen 85-99 % der Betroffenen nach 10 Jahren auf der Symptomebene nahezu remittieren (Übersicht in [19,21] [24,25]. Im Gegensatz dazu berichten 30-50 % aller im stationären kinder-und jugendpsychiatrischen Hilfesystem befindlichen Jugendlichen, sich repetitiv selbst zu verletzen [26].…”
Section: Meta-analysenunclassified
“…A single item question rendered a prevalence rate of 17% in a study measuring DSH, without differentiating on the basis of intent (Landstedt & Gillander Gådin, 2011). Internationally, prevalence rates of NSSI in community samples of adolescents usually range somewhere between 13-25% around the world (Baetens et al, 2011;Brunner et al, 2007;Brunner et al, 2014;Guan et al, 2012;Hankin & Abela, 2011;Jacobson & Gould, 2007;Laye-Gindhu & Schonert-Reichl, 2005;Martin, Swannell, Hazell, Harrison, & Taylor, 2010;Muehlenkamp & Gutierrez, 2004;Muehlenkamp, Williams, Gutierrez, & Claes, 2009;Nixon, Cloutier, & Jansson, 2008;Plener, Libal, Keller, et al, 2009;Plener et al, 2013;Tolmunen et al, 2008;You, Leung, Fu, & Lai, 2011;Zoroglu et al, 2003). However, both higher (Cerutti, Manca, Presaghi, & Gratz, 2011;Lloyd-Richardson et al, 2007;Lundh, Karim, & Quilisch, 2007;Yates, Carlson, & Egeland, 2008) and lower (Hilt, Nock, Lloyd-Richardson, & Prinstein, 2008;Patton et al, 2007;Prinstein et al, 2010) estimates have also been found, the latter sometimes due to younger samples.…”
Section: Nssimentioning
confidence: 99%
“…To fully understand health and illness, the Biopsychosocial Model (which imposes evaluating and framing the patient within a multiaxial system) must systematically be considered from a developmental perspective [7,8]. It is of the outmost importance to identify the various factors involved in the pathological process: protection and resilience factors, risk and vulnerability factors, precipitating and maintenance factors (Stress-vulnerability Model) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%